Studies on Anopheles (Kerteszia) homunculus Komp (Diptera: Culicidae) - Sallum, Maria Anice Mureb; Santos, Cecilia L. S. Dos; Wilkerson, Richard C. (Zootaxa, 2009)
The present findings suggest that Anopheles (Kerteszia) homunculus may comprise more than one species. The rDNA ITS2 sequence data corroborate the presence of An. homunculus l.s. in Mata Atlântica, southern Brazil, and suggest that specimens from Trinidad may belong to an unnamed morphologically similar species. There is a need for additional studies to establish the geographical distribution of An. homunculus l.s. in continental South America and in Trinidad, especially in southern Mata Atlântica, Brazil.